FIRM ATTRIBUTES AND STOCK PRICE OF LISTED FINANCIAL SERVICE FIRMS IN NIGERIA - Dr. Ibrahim Lawal; Prof. Joshua Okpanachi; Prof. Agbi Eniola Samuel; Dr Suleiman Tauhid (Gusau Journal of Accounting and Finance, 2025)
The Nigerian financial services sector, a critical component of the nation's economy, faces challenges in navigating the intricate interplay between share prices, dividend policies, and leverage. Despite the sector's pivotal role in mobilizing long-term resources and sustaining investor confidence, there exists a gap in understanding how specific firm attributes, particularly dividend policy and leverage, influence share prices over an extended period. Therefore, this research aims to address these gaps by examining the intricate relationships between dividend policy, leverage, and share prices in Nigerian financial service firms over a 15-year period from 2008-2022, employing robust methodologies for a more comprehensive and applicable understanding of the challenges and opportunities in the sector. The theoretical framework draws on signaling theory, providing insights into the complexities of stock prices and the strategic use of signals by managers. The study's employed correlation research design, multiple regressions on panel data, and robustness tests to ensure the validity and reliability of the statistical inference. The findings reveal a significant inverse relationship between share prices and leverage, emphasizing the importance of prudent debt structure management for investor confidence. Conversely, a significant and positive correlation is observed between share prices and dividend policy, underscoring the potential value enhancement through a robust dividend distribution plan. Based on the findings, the study recommended that, management should highlight the need for financial institutions to strike a balance between meeting obligations and minimizing risk exposure. Transparent communication, optimal debt management, and cultivating strong dividend policies are crucial. Policymakers and regulators should consider these findings to create a more robust and investor-friendly financial environment in Nigeria.